Pengaruh Pemberian Pupuk Organik Terhadap Pertumbuhan Tanaman Porang di Kelurahan Darma, Kabupaten Polewali Mandar - Hasri, Mutmainnah; Rusmidin; Irundu, Daud; Idris, Andi Irmayanti; Suparjo Razasli Carong; Indhasari, Fitri (Pangale Journal of Forestry and Environment, 2023)
This research aims to identify the most effective treatment for the growth of porang plants. The study employs a Randomized Group Design (RAK) and analyzes data using ANOVA with the SPSS application. The results indicate that the treatments applied to porang seedlings exhibit a highly significant interaction with the development of plant diameter across different seedling sizes (small, medium, and large), with significance values less than 0.05. Similarly, all treatment groups demonstrate a highly significant interaction with the development of plant height and diameter in each group of porang seedlings, with all significance values being less than 0.05. The optimal treatment identified is treatment B for both plant height and diameter. Additionally, group 2 is the best performing group for plant height and diameter. Key words: Porang plant, treatment, organic fertilizer